Update on Hepatitis C 2017
DOI: 10.5772/intechopen.70729
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Direct-Acting Antiviral Agents in Treatment of Hepatitis C Virus Infections

Abstract: Compounds targeting nonstructural (NS) proteins of hepatitis C virus (HCV) demonstrate clinical promise, suggesting that NS3/NS4a, NS5A, or NS5B inhibitors are potential components in direct-acting antiviral (DAA) combination therapies. In vitro studies revealed dramatic inhibition of viral replication or alteration in subcellular localization of NS proteins. DAAs bind either to catalytic sites (NS3 and NS5B) or to domain-1 of NS5A. Although >90% of the patients clear HCV RNA from their sera, a significant por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…37 Baricitinib treatment of HBV infected ICOs resulted in an increase (approximately 1 log) in HBV RNA suggesting that HBV replication is sensitive to innate activation of antiviral responses and is consistent with studies showing that HBV can be cleared from the liver in a cytokine-mediated nontoxic manner 26,38 and as a result of interferon dependent antiviral responses. 39 Given that the JAK-STAT signaling The ability of HBV to induce a robust antiviral response is controversial with inconsistent reports on the ability of HBV to activate and evade the innate antiviral response. 40,41 This is primarily due to the limitations of model systems used to investigate HBV replication such as hepatoma derived cell lines (i.e., HepG2) that have defects in innate immune sensing and associated signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…37 Baricitinib treatment of HBV infected ICOs resulted in an increase (approximately 1 log) in HBV RNA suggesting that HBV replication is sensitive to innate activation of antiviral responses and is consistent with studies showing that HBV can be cleared from the liver in a cytokine-mediated nontoxic manner 26,38 and as a result of interferon dependent antiviral responses. 39 Given that the JAK-STAT signaling The ability of HBV to induce a robust antiviral response is controversial with inconsistent reports on the ability of HBV to activate and evade the innate antiviral response. 40,41 This is primarily due to the limitations of model systems used to investigate HBV replication such as hepatoma derived cell lines (i.e., HepG2) that have defects in innate immune sensing and associated signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 The previous reports have shown that treatment of hepatitis C with dasabuvir is associated with mutations including S556G and C316Y mutations in the viral NS5B polymerase, leading to resistance. 20,21 Increased damage indexes and frequencies have been observed in the brain of mice treated with efavirenz, 23 and findings from this study showed that efavirenz is a highly tumorigenic agent but not mutagenic nor irritant (Supporting Information 1). The tumorigenic effect of efavirenz may be responsible for adverse effects (e.g., headache, dizziness, insomnia, impaired concentration, agitation, amnesia, fatigue, and hallucinations) of efavirenz on the central nervous system.…”
Section: ■ Introductionmentioning
confidence: 70%
“…Again, they have shown some unfavorable therapeutic outcomes. For example, dasabuvir and tipranavir have been associated with mutations in hepatitis C NS5B polymerase and human immunodeficiency virus (HIV) protease, respectively, leading to resistance. Increased damage indexes and frequencies have been observed in the brain of mice treated with efavirenz, and WHO guidelines do not recommend efavirenz use during the first trimester of pregnancy due to concern for teratogenicity . Therefore, there is a need to discover/identify more potent and nontoxic/safer derivatives of the parent compounds.…”
Section: Introductionmentioning
confidence: 99%
“…38 Baricitinib treatment of HBV-infected ICOs resulted in an increase (approximately 1 log) in HBV RNA suggesting that HBV replication is sensitive to innate activation of antiviral responses and is consistent with studies showing that HBV can be cleared from the liver in a cytokine-mediated nontoxic manner 27,39 and as a result of interferon dependent antiviral responses. 40 Given that the JAK-STAT signaling pathway plays a role in signal transduction for a number of key cytokines a number of possible mechanisms are possible. Interleukin-6 plays an important role in hepatocyte homeostasis and its impairment can lead to impaired innate responses to viral infection while disruption of interferon signaling, that is important for an antiviral state through production of antiviral ISGs may explain the increase in HBV replication following inhibition of Jak1 and 2 by Baricitinib.…”
Section: Discussionmentioning
confidence: 99%